Jaggery based spray as a potential tool in improving natural enemies on maize against Spodoptera frugiperda (Journal of Agriculture and Biology, 2025)
Fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a significant pest of maize in Asia and Africa. The excessive use of synthetic insecticides causes concerns of resistance, environmental pollution and reduction of natural enemies. New mechanisms that have potential to be effective include conservation biological control approaches that improve the activity of predators and parasitoids. This research determined the impacts of sugar sprays using jaggery in the abundance of arthropod predators and pests, such as S. frugiperda, in maize fields in Pakistan (Multan) across two agricultural seasons (autumn and spring). Four treatments (Prototype treatment) of full-dose of jaggery spray (17 kg ha-1), half-dose of jaggery spray (8.5 kg ha-1), water spray and an untreated control were done in a replicated field setup. Before and after the weekly applications, the predator and pests of arthropods were measured through standardized plant-based sampling and the maize damage against the S. frugiperda predator was measured with the use of the Davis leaf damage scale. Plots that had been treated with jaggery had always greater abundances of generalist predators; specifically, ants, spiders, rove beetles, and ladybird beetles than did water-sprayed and untreated plots. These results show that jaggery-based sugar sprays have the capacity to stimulate predator activity in maize agroecosystems but they do not give conclusive results on the efficiency to suppress the population of S. frugiperda when applied individually. Sugar sprays can therefore be useful in conservation biological control as an additional technique in integrated pest management initiative, and not as an isolated control mechanism.